Mortality of young offenders: a national register-based follow-up study of 15- to 19-year-old Finnish delinquents referred for forensic psychiatric examination between 1980 and 2010 - Lindberg, Nina (Child Adolesc Psychiatry Ment Health, 2017)
BACKGROUND: The mortality rate of young offenders is high. Furthermore, mortality in young offenders is associated with psychiatric and substance use disorders. The primary aim of this national register-based follow-up study was to investigate the mortality rate of Finnish delinquents who underwent a forensic psychiatric examination between 1980 and 2010. As delinquency is not a solid entity, we further aimed to compare the risk of premature death among different subgroups of the delinquents; violent versus non-violent offenders, offenders with alcohol use disorders versus those with no such diagnoses, offenders with schizophrenia spectrum disorders versus conduct- and personality-disordered offenders, under-aged versus young adult offenders, and, finally, boys versus girls. METHODS: We collected the forensic psychiatric examination reports of all 15- to 19-year-old offenders who were born in Finland and had undergone the examination between 1.1.1980 and 31.12.2010 (n = 606) from the archives of the National Institute of Health and Welfare and retrospectively reviewed them. For each delinquent, four age-, gender- and place of birth-matched controls were randomly selected from the Central Population Register (n = 2424). The delinquents and their controls were followed until the end of 2015. The median follow-up time was 23.9 years (interquartile range 15.3–29.5). We obtained the mortality data from the causes of death register. Deaths attributable to a disease or an occupational disease were considered natural, and those attributable to an accident, suicide or homicide were considered unnatural. RESULTS: By the end of the follow-up period, 22.1% (n = 134) of the delinquents and 3.4% (n = 82) of their controls had died (OR 8.11, 95% CI 6.05–10.86, p < 0.001). Among boys, 22.0% (n = 121) of the delinquents and 3.7% (n = 81) of the controls had died (OR 7.38, 95% CI 5.46–9.95, p < 0.001). Male delinquents’ risk of unnatural death was almost 11-fold, of natural death more than twofold, and of unclear death more than fourfold compared to that of their controls. No girls had natural or unclear deaths, but 23.6% (n = 13) of the delinquents and 0.5% (n = 1) of the controls had died due to unnatural causes (OR 67.79, 95% CI 8.63–532.00, p < 0.001). The violent delinquents’ risk of premature death was twice that of the non-violent delinquents. The other comparisons demonstrated no statistically significant differences between subgroups. CONCLUSIONS: Even though the Finnish correction system prefers psychiatric treatment and rehabilitation over criminal sanctions, and the national health care system offers developmental-phase-specific psychiatric care, the mortality rate of delinquents, especially of those with a history of violent offences, is high. The excess mortality of offenders can be regarded as a specific public-health inequity that calls for more effective intervention procedures than those used thus far.